Testing the Effect of different acceptable Accounting alternatives on Lending Decisions of Commercial Bankers - EL-ARABI, ABDUSSALAM (Dirasat in Economics and Business, 1981)
Accounting has been defined as a measurement and communication process to provide relevant information about an entity to enable users of information to make informed decisions leading to optimal allocation of scarce resources and to accomplish their objectives. In recent years there has been substantial dissatisfaction with the current accounting product on the part of a variety of people. One of the major criticisms is that acceptable accounting principles applicable to any transaction or group of transactions are so numerous that comparison between companies is distorted by the lack of common measuring devices. Accounting literature abounds with the pros and cons of narrowing the areas of accounting alternatives. On one hand, there are some who maintain that uniformity is necessary for financial statements comparability. Others insist that flexibility must be maintained because no two entities are indentical and different procedures and methods are necessary to depict results of different entities. l Also it has been argued that by disclosing all pertinent information about accounting policies, the users of the financial statements will be able to adjust their decisions based on the information disclosed.